Analisis Model Makro Ekonomi Regional Bali Pendekatan Solow Neclassical Growth - Budhiasa, Gede Sudjana (Jurnal Kajian Ekonomi dan Keuangan, 2012)
Bali Island is the most popular tourist destination in Indonesia, therfore the growth for international tourist destionation to Bali island could be impact and supporting generating income of people of Bali island. However, the policy design of one for all that was design by BTDC projects were concentrated tourist destionation at Kabupaten Badung and Kota Denpasar as main region activities.This research have been found that using econometrics two stages regression methods indicated that tourist growth center policy of BTDC is failures to distribute income and other benefits to the suburb area of 7 Kabupaten outside from center growth Kabupaten Badung and Kota Denpasar. The failure of beneficial of 7 Kabupaten to take participation is that because of the economic structure of 7 Kabupaten become dominated of primary sector and less power of industrial sectors